2009
DOI: 10.1002/chin.200936053
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Mild and Efficient DBU‐Catalyzed Amidation of Cyanoacetates.

Abstract: Nitriles P 0350Mild and Efficient DBU-Catalyzed Amidation of Cyanoacetates. -This method can be applied to prepare complex cyanoacetamides of type (V) which display potent immunosuppressant activity. -(PRICE, K. E.; LARRIVEE-ABOUSSAFY, C.; LILLIE, B. M.; MCLAUGHLIN, R. W.; MUSTAKIS, J.; HETTENBACH, K. W.; HAWKINS, J. M.; VAIDYANATHAN*, R.; Org. Lett. 11 (2009) 9, 2003-2006; Chem. Res. Dev., Pfizer Inc., Groton, CT 06340, USA; Eng.) -Jannicke 36-053

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Initially the group found that DBU(5) accelerated the rate of amidation of ethyl cyanoacetate (39) with a small range of secondary amines (Scheme 6a). 16 This methodology was extended by using DBU (5) to catalyse the addition of amines to acyl imidazole 42, which was formed in situ from the reaction of 2-methyl-2-phenyl propanoic acid (41) with N,N'-carbonyldiimidazole (CDI) (Scheme 6b). 17 This sterically demanding substrate was chosen to demonstrate the efficiency of DBU (5) as a catalyst for difficult substrates and also to avoid sidereactions that could occur via -deprotonation.…”
Section: Amidationsmentioning
confidence: 99%
“…Initially the group found that DBU(5) accelerated the rate of amidation of ethyl cyanoacetate (39) with a small range of secondary amines (Scheme 6a). 16 This methodology was extended by using DBU (5) to catalyse the addition of amines to acyl imidazole 42, which was formed in situ from the reaction of 2-methyl-2-phenyl propanoic acid (41) with N,N'-carbonyldiimidazole (CDI) (Scheme 6b). 17 This sterically demanding substrate was chosen to demonstrate the efficiency of DBU (5) as a catalyst for difficult substrates and also to avoid sidereactions that could occur via -deprotonation.…”
Section: Amidationsmentioning
confidence: 99%
“…Distilled off the solvent and a pale yellow solid (compound 1) was isolated (10.8 g), theoretical yield 45 %. 38,39,40 In a 20 mL RB flask equipped with reflux condenser, thermo socket, magnetic stirrer and addition funnel, ethyl-2-cyano acetate(1.0 g, 0.0088 mol) is mixed with benzyl amine (1.13 g, 0.0106 mol) in 10 ml ethanol medium under reflux for 1.0 hr. The reaction mixture was cooled to room temperature.…”
Section: Scheme-1: Chemical Path For the Synthesis Of Desired Compounmentioning
confidence: 99%